Novel method of combined photon beam radiotherapy and brachytherapy for treatment of extensive advanced scalp squamous cell carcinoma - Farzin, Mostafa; Jaberi, Ramin; Jafari, Fatemeh; Najafi, Mohsen; Kolahdouzan, Kasra (Journal of Contemporary Brachytherapy, 2021)
Radiotherapy of extensive malignant scalp lesions has always been a challenge for radiation oncologists considering the proximity of critical structures. We treated a 39-year-old patient with extensive scalp squamous cell carcinoma with application of adjuvant concurrent chemoradiation and external beam radiation therapy (EBRT), followed by high-dose-rate (HDR) surface brachytherapy boost using an exclusively designed mould, and assessed the radiation dose reaching planning target volume, brain, and optic structures. Comparison between conventional planning with sole EBRT and combined treatment planning with EBRT and brachytherapy, assured the use of the latter treatment to avoid high radiation doses from reaching critical organs at risk without compromising the required dose for planning target volume.